Spatio-temporal Distribution Characteristics and Future Trend Analysis of Extreme Climate Indices in Nenjiang River Basin over the Past 60 Years - GONG Xiao; DAI Changlei; LI Shuling; XIAO Yue (Renmin Zhujiang)
The study of extreme climate change in the Nenjiang River Basin is of great significance for ensuring ecological security and agricultural production. Based on the observation data such as daily temperature and precipitation from 12 meteorological stations in the Nenjiang River Basin between 1960 and 2020, this paper selects 26 extreme climate indices. Meanwhile, methods like the linear fitting, Mann-Kendall mutation test, and sliding T-test are adopted to analyze the spatio-temporal variation characteristics of extreme temperature and precipitation in the basin. Additionally, this paper utilizes the NEX-GDDP-CMIP6 dataset to predict future climate change trends in the basin. The results show that from 1960 to 2020, the extreme warm index significantly increases, while the extreme cold index significantly decreases, with mutation years mainly concentrated in the years after 1975. The extreme precipitation index significantly rises, with mutation years primarily in the years after 2010. In terms of spatial distribution, the areas with high-value extreme cold indices are mainly located in the Oroqen Autonomous Banner, while the areas with high-value extreme warm indices are more scattered. In addition to the intensity indices, other areas with high-value extreme precipitation indices are also concentrated in the Oroqen Autonomous Banner. In the future, the Nenjiang River Basin is expected to show a warming trend in temperature and a rising trend in precipitation, with an increased probability of extreme high-temperature events and extreme precipitation events.